Special education among children with autism spectrum disorder (Journal of Advances and Scholarly Researches in Allied Education, 2024)
For children with autism spectrum disorder (ASD), special education is essential to improving their development and learning. This study examines the most recent strategies and techniques used in individualized education plans (IEPs), applied behavior analysis (ABA), and sensory integration treatment for children with ASD in special education. A review of current research and case studies is used to assess how successful various methods are. The study also addresses the difficulties that educators and caregivers have when putting these ideas into practice, such as the lack of resources and the need for specialized training. The evaluation emphasizes the value of working together as a team with educators, parents, and healthcare providers to create and carry out successful education programs for kids with ASD.